Impact of industrial effluent on water quality at the Belat River, Kuantan - Nurul Zafirah, Othman (2015)
Industrial wastewater entering a water body represents a heavy source of environmental pollution in the Belat River. It affects both the water quality as well as the microbial and aquatic flora. The objectives of this study were to determine the effects of industrial activities on water quality in the Belat River and classify the river water based on Water Quality Index (WQI) and National Water Quality Standards (NWQS) Malaysia. Surface waters were sampled from February until March 2015 to access the water quality of the river. Results revealed that industrial waste water are the main source of pollutants in the study area. The study also showed that the station 1 and 2 were slightly polluted and classified as class III, while station 3 was polluted and classified as class IV. A study of water quality in the Belat River need to be done by certain parties in the future so that the data obtain can be compared from time to time.